COVID-19 and Cardiovascular System: Pathophysiology, Pathomorphology, Complications, Long-Term Prognosis - S. S. Petrikov; A. A. Ivannikov; M. K. Vasilchenko; A. N. Esaulenko; Kh. G. Alidzhanova (Неотложная медицинская помощь)
Like other respiratory viruses, COVID-19 has extrapulmonary manifestations. The effect of the virus leads to the cardiovascular system (CVS) damage in particular, which pathophysiological mechanisms are not fully understood. In this article we analyze modern ideas about COVID-19, consider possiblelinks of pathogenesis, make an attempt to systematize pathophysiological mechanisms of cardiovascular impairment and its complications, analyze the relation with cardiovascular comorbidity, describe pathomorphological features and discuss possible long-term prognosis. The information in this article can contribute to understanding the two-way interaction of cardiovascular diseases and the effects of COVID-19 in order to develop effective preventive measures and make the right decision in choosing therapeutic tactics for a patient.